2013
DOI: 10.1371/journal.pone.0060516
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Beclin 1 Correlates Closely with Bcl-xL Expression and Poor Prognosis of Ovarian Carcinoma

Abstract: BackgroundIt has been suggested that autophagy-related Beclin 1 plays a critical role in the regulation of tumor development and/or progression, but its prognostic significance and relationship with Bcl-xL expression in ovarian carcinoma are unclear.Methodology/Principal FindingsIn the present study, the methods of Western blotting and immunohistochemistry (IHC) were utilized to investigate the expression status of Beclin 1 and Bcl-xL in fresh ovarian tissues and paraffin-embedded epithelial ovarian tumor tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 40 publications
6
47
1
Order By: Relevance
“…Therefore, an increased frequency of follow-up in patients with loss of BECN1, to detect recurrence earlier, may allow patients to quickly receive further beneficial cytoreductive surgery or second-line chemotherapy. Multiple previous studies have demonstrated comparable data in line with the present study, in that the loss of BECN1 was reported to be associated with an unfavorable prognosis of several solid cancers, including ovarian carcinoma (15,(25)(26)(27). In contrast, other studies demonstrated that the loss of BECN1 was significantly correlated with improved survival in patients with endometrial cancer, renal cell cancer, and colorectal cancer (28)(29)(30).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, an increased frequency of follow-up in patients with loss of BECN1, to detect recurrence earlier, may allow patients to quickly receive further beneficial cytoreductive surgery or second-line chemotherapy. Multiple previous studies have demonstrated comparable data in line with the present study, in that the loss of BECN1 was reported to be associated with an unfavorable prognosis of several solid cancers, including ovarian carcinoma (15,(25)(26)(27). In contrast, other studies demonstrated that the loss of BECN1 was significantly correlated with improved survival in patients with endometrial cancer, renal cell cancer, and colorectal cancer (28)(29)(30).…”
Section: Discussionsupporting
confidence: 90%
“…However, it has been reported by Lin et al that decreased BECN1 expression is correlated with shortened survival in ovarian cancer patients, 30 which is in contrast with our data. The reason is unclear, but the proportion of patients with Grade 3 (23.7%, 40/169 cases) was lower in Lin's report than those in our series (63.1%, 99/157 cases).…”
Section: (C) (Line Mock) Plasmid; (E and F)contrasting
confidence: 99%
“…Furthermore, ceramide has also been found to cause autophagy which results in either cell survival or death (14). Previous research has reported that ceramide caused COX-2-dependent apoptosis in ovarian cancer OVCAR-3 cells (15). In the present study, C2-ceramide did not only induce cell apoptosis, but also autophagy.…”
Section: Discussionsupporting
confidence: 62%